Copper revolution - Améstica, Luis (Base Diseño e Innovación, 2015)
Andean Copper is the Chilean company that discovered the innovation that revolutionized the copper industry: polymers containing the red metal. Thanks to them it is possible to apply the antimicrobial properties of copper to surfaces such as fabrics, melamine and creams.